Fujinon intelligent color enhancement for the diagnosis of early esophageal squamous cell carcinoma and precancerous lesion - Li, Yan-xia; Shen, Lei; Yu, Hong-gang; Luo, He-sheng; Yu, Jie-ping (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Esophageal squamous cell carcinoma is a common malignant tumor in recent years, and thekey for improving the survival rate is early diagnosis and treatment. Computed virtual chromoendoscopy with the Fujinon intelligent color enhancement (FICE) system was reported to improve visualization of neoplastic and nonneoplastic lesions in gastroscopy and colonoscopy. The purpose of this study was to evaluate the value of FICE in the diagnosis of early esophageal squamous cell carcinoma and precancerous lesions. Materials and Methods: Two hundred fifty-seven patients with suspicious lesions of the esophagus were examinedsuccessively by FICE, magnifying FICE, Lugol chromoendoscopy, and magnifying Lugol chromoendoscopy in the hospital. The lesions and the intrapapillary capillary loop (IPCL, microvessels at the surface of esophageal carcinoma) were observed and compared with the pathologic diagnosis that was regarded as the golden standard. Results: The positive rates of early esophageal squamous cell carcinoma were 92.6% and 88.9% as examined by FICE and Lugol chromoendoscopy (p>0.05), and 96.3% and 92.6% as examined by magnifying FICE and magnifying Lugol chromoendoscopy (p>0.05), respectively. The magnifying FICE could observe the IPCL of the esophagus clearly. Early esophageal squamous cell carcinoma and high-grade intraepithelial neoplasia were mainly type IV and type V. Low-grade intraepithelial neoplasia and esophagitis were type II and type III, and normal esophagus was type I; however, the observation of the IPCL by magnifying Lugol chromoendoscopy was not clear. Conclusion: Fujinon intelligent color enhancement and magnifying FICE are complements to Lugol chromoendoscopy and magnifying Lugol chromoendoscopy in the diagnosis of early esophageal lesions.